The Implementation of Fingerprint Attendance Systems and Organizational Culture in Enhancing Work Discipline - Lingga Yonita (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Improving employee work discipline is a crucial factor in supporting the effectiveness of public service delivery, particularly at the urban village (Kalurahan) government level. In an effort to improve employee discipline, the Head of Pulau Harapan urban village implemented a fingerprint-based attendance system as a form of technological utilization in personnel management. This system is expected to create order, increase compliance with working hours, and minimize fraudulent practices related to employee attendance. This study aims to analyze the implementation of the fingerprint attendance policy as well as the role of leadership and organizational culture in improving employee work discipline. This research employs a descriptive qualitative approach. Data were collected through observation, in depth interviews, and documentation involving sub district officials who are directly engaged in the implementation of the fingerprint attendance system. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. Data validity was ensured through prolonged observation and methodological triangulation. The results of the study indicate that the implementation of the fingerprint attendance policy has been properly executed and has proven effective in improving employee work discipline. Organizational culture also shows a positive and significant effect on work discipline, suggesting that a strong organizational culture encourages disciplined and professional work behavior. Conclusion, fingerprint attendance and organizational culture exert a positive influence on employee work discipline. Therefore, the implementation of attendance technology supported by effective leadership and a strong organizational culture is able to create a more disciplined, efficient, and accountable work environment.